DMR (Dam Mass Rating). An adaption of RMR geomechanics classification for use in dams foundations - R. Romano (The Southern African Institute of Mining and Metallurgy, 2003)
Some topics, which difficult the effective use of RMR for dam foundations, are reviewed and a new geomechanics classification system, DMR (Dam Mass Rating), is proposed -as an adaptation of RMR- giving guidelines for several practical aspects in dam engineering and appraisal of dam foundation. On revise quelques problems qui ont fait difficile l’application du RMR pour les fondations des barrages. On propose un nouveau classification système, DMR (Dam Mass Rating)-comme un désarroi du RMR-qui donne recommendations pour quelques problèmes pratiques dans le projet et construction des barrages, et de ses fondations. Es werden einige die praxisgerechte Nutzung des RMR (Rock mass Rating) erschwerende Themen betrachtet und ein neues Geomechanisches Einteilungssystem, das DMR (Dam Mass Rating), eine Anpassung des RMR, vorgeschlagen. Daraus resultieren neue Richtlinien für verschiedene praktische Aspekte beim Dammbau und bei der Beurteilung von Dammunterbauten